El yacimiento romano de “Los Villaricos” (Mula, Murcia). Aproximación al estudio de un establecimiento rural de época romana en la Región de Murcia - Lechuga Galindo, Manuel; Amante Sánchez, Manuel (Antigüedad y Cristianismo, 1991)
The site known as "Arreaque" o "Los villarkos" is situated on the left bank of the river Mula in Murcia. In this location is a r u r a l Roman establishment which extends along a gentle slope which is interrupted in the southwestern end by an abrupt precipice caused by the erosion of the afore mencioned river. Now in the process of being excavated, it is worth mencionlng the identification of the PARS URBANA, which has its own termal instalation and the PARS RUSTICA, where there have been discovered instalations dedicated to the production of oil, evidence of at least part of the economic activity of this site. The chronology extends from at least the second half of the first century A.D. until the second half of the fifth century A.D. The final disposition, or layout, of the site was established between the last half of the second century A.D. and the beginning of the third century, with evidence of the amortization of the industrial oil producing instalation. After the last half of the fifth century A.D. it has been documented its use as a necropolis, using part of the existing structures for this purpose.